Organizional-pedagogical conditions of multiculturalism in Kazakhstan - Zhetpisbaeva, B.А.; Shelestova, T.Yu.; Ospanova, A.K.; Zhankina, B.Zh. (KU Publ., 2021)
The article is devoted to the problem of organizational and pedagogical conditions in the framework of trilingual education in the Republic of Kazakhstan. The authors consider the essence of the concepts of “conditions”, “pedagogical conditions”, “organizational and pedagogical conditions”, “structure of organizational and pedagogical conditions” in more detail. Psychologists consider the concept of “conditions” in the context of mental development through a set of internal and external causes that determine the overall psychological development of a person, accelerating and slowing it down, influencing the development process, its dynamics and final results. Pedagogical condition is a general scientific one, and its essence in the pedagogical aspect can be characterized in several provisions: 1. A condition is a set of causes, circumstances, any objects, etc. 2. The influence of conditions can accelerate and slow down the processes of development, education and training, as well as affect their dynamics and final results. 3. Caracterized complex influence on the developing, education and studying of a person. The organizational-pedagogical conditions and its’ structure were defined, from the perspective of language education, which is based on problem of investigation of the succession of the multiculturalism in the Republic of Kazakhstan.
Қазақстандағы мультимəдениеттіліктің ұйымдастырушылық-педагогикалық шарттары
Организационно-педагогические условия мультикультурализма в Казахстане
Keywords: multiculturalism; condition; pedagogical condition; socio-pedagogical condition; organizationalpedagogical condition; trilingualizm; multiculturalism; polylingual education